2022
DOI: 10.7126/cumudj.1032492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Repolishing Procedures on The Color Change of Alkasite

Abstract: Objectives: An esthetic restoration with an unacceptable color is the main cause for replacement of anterior tooth restorations. The aim of this study is to evaluate the effect of repolishing on the color change of the new material group of alkasite after exposure to coffee solution. Materials and Methods: Alkasite material placed in Teflon molds with a diameter of 8 mm and a height of 2 mm was polymerized under the application of mylar strip and a total of 32 samples were obtained. The samples were randomly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Discoloration in composites can be due to internal and external factors. Internal factors include self-coloring of the resin material and oxidation or hydrolysis in the resin matrix ( 4 ). External factors such as discoloration resulting from exposure to coloring agents and their absorption by the material, as well as the degree of staining varying with oral use, can cause changes in resin-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discoloration in composites can be due to internal and external factors. Internal factors include self-coloring of the resin material and oxidation or hydrolysis in the resin matrix ( 4 ). External factors such as discoloration resulting from exposure to coloring agents and their absorption by the material, as well as the degree of staining varying with oral use, can cause changes in resin-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The surface texture of a tooth-colored restoration can have a significant impact on plaque formation, discoloration, wear, and the overall esthetic appearance of the restoration. Therefore, proper finishing and polishing are critical procedures that can increase both the aesthetics and lifespan of restored teeth ( 4 ). Recent studies have shown that resin composites, which are commonly used for tooth restoration exhibit less discoloration after finishing and repolishing ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation